If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 3 = 612x Combine like terms: 9 + 3 = 12 12 = 612x Solving 12 = 612x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-612x' to each side of the equation. 12 + -612x = 612x + -612x Combine like terms: 612x + -612x = 0 12 + -612x = 0 Add '-12' to each side of the equation. 12 + -12 + -612x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -612x = 0 + -12 -612x = 0 + -12 Combine like terms: 0 + -12 = -12 -612x = -12 Divide each side by '-612'. x = 0.01960784314 Simplifying x = 0.01960784314
| -1.23x=-456 | | 16x+3=18x+2 | | 2q=26 | | 11x=7x+12 | | 9+3+x=612*x | | 0.1x+0.5y=-1.3 | | 3(x-7)+20=-2+6x+1 | | 16x+3=18+2 | | 8a-7=7+a | | 3x-8=2+X | | 9+3+x=612 | | -11+19x=19x-11 | | 1.5d+8.25=3+3.25d | | 15b=a | | 2t-7=t-2 | | h+9.2=-9.2 | | -5p+39=14 | | 3-10b=2b-a | | 2x-11+3x-14=15 | | 8(10x-10)=85x+500 | | 3(x-4)+7x=24+x | | 3(x-1)=4x+8 | | 7x-13=x+8 | | 8v-6v=10 | | 4(r-8)=8(r-5) | | 5-3n=41 | | -2-x=10 | | -(-2x-4)+5=26 | | 24-2w=33 | | 22-30=x | | 5x-8y=-11 | | 30=b-9+6b |